(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Family of a child with disabilities faces several social risks at the same time, child developmental challenges on one hand, and obtaining appropriate support from the relevant institutions, on the other. As a country in a long transition, we still do not have appropriate system of formal and informal social support, or it functions at an unsatisfactory level, due to which families face a series of additional problems. The aim of our research is to give an overview of the social legislation for improving quality of life of a child with disabilities and his/her family. We try to determinate the financial benefits offered by the state and identifying eventual discrimination in the legal regulation. According to the obtained results, we found that there are several discriminatory decisions in the allocation of benefits. One of those benefits is the special allowance which according to the latest changes it value is 5.096 den for 2019. It is intended for several categories of disability, but not for persons with mild intellectual disability, which is a kind of discrimination because this category of children is the most numerous among children with intellectual disability, and on the other hand usually they come from families with the lowest social and economic status.